1995
DOI: 10.1007/bf00241497
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic study of synaptogenesis and myelination of the olfactory centers in developing rats

Abstract: Development of the central olfactory system was studied in the rat with an electron microscope at three main structures: the olfactory bulb, the lateral olfactory tract, and the primary olfactory cortex (the piriform cortex). As a parameter of development, the synaptic density was examined quantitatively in the bulbar glomerulus and layer Ia (termination of bulbofugal fibers) of the piriform cortex. which are the key stations of the olfactory pathway. The synaptic densities in the glomerulus and those in layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…These results suggest that ectopic myelination occurred after neonatal LOT injuries, irrespective of the lesion sizes. Myelination of LOT occurs between P7 and P21 [13,16];…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that ectopic myelination occurred after neonatal LOT injuries, irrespective of the lesion sizes. Myelination of LOT occurs between P7 and P21 [13,16];…”
Section: Discussionmentioning
confidence: 99%
“…The lateral olfactory tract (LOT) is the main fiber tract of the central olfactory system and connects the olfactory bulb to multiple ventrobasal cortical areas, which are collectively known as the olfactory cortices [1,7,13,14,17,18]. Generally, LOT is macroscopically observed as a white myelinated band on the basal surface of the brain in adult rats.…”
Section: Introductionmentioning
confidence: 99%
“…EM observations confirm the absence of synapses between pyramidal cells of olfactory cortex and the LOT at E15, but later ages were not examined (Derer et al, 1977). In the rat, EM examination revealed that piriform layer 1a synapses first appear infrequently at E19, coincident with E19 formation of glomeruli in rat (Schwob and Price, 1984), increasing in density with age to almost 40% of adult levels by P10 (Moriizumi et al, 1995). …”
Section: Olfactory Systemmentioning
confidence: 99%
“…1). Within the CNS a sequential, peripheral-to-central, pattern for connectivity is observed for the olfactory system, with initial connectivity between OSNs and MT cells at E15 (Blanchart et al, 2006; Hinds and Hinds, 1976), and initial connectivity between LOT and primary olfactory cortex at E16 (Moriizumi et al, 1995; Schwob and Price, 1984). Therefore, anatomical evidence is consistent with the possibility that peripheral activity could play an instructive role during synaptogenesis at both glomeruli and primary olfactory cortex.…”
Section: Unresolved Issues In Sensory System Developmentmentioning
confidence: 99%
See 1 more Smart Citation